Differences in systemic and mucosal SARS-CoV-2 antibody prevalence in a prospective cohort of Dutch children - Keuning, Maya W.; Grobben, Marloes; Bijlsma, Merijn W.; Anker, Beau; Berman-de Jong, Eveline P.; Cohen, Sophie; Felderhof, Mariet; de Groen, Anne-Elise; de Groof, Femke; Rijpert, Maarten; van Eijk, Hetty W. M.; Tejjani, Khadija; et al. (Frontiers in Immunology, 2022)
Background As SARS-CoV-2 will likely continue to circulate, low-impact methods become more relevant to monitor antibody-mediated immunity. Saliva sampling could provide a non-invasive method with reduced impact on children. Studies reporting on the differences between systemic and mucosal humoral immunity to SARS-CoV-2 are inconsistent in adults and scarce in children. These differences may be further unraveled by exploring associations to demographic and clinical variables. Methods To evaluate the use of saliva antibody assays, we performed a cross-sectional cohort study by collecting serum and saliva of 223 children attending medical services in the Netherlands (irrespective of SARS-CoV-2 exposure, symptoms or vaccination) from May to October 2021. With a Luminex and a Wantai assay, we measured prevalence of SARS-CoV-2 spike (S), receptor binding domain (RBD) and nucleocapsid-specific IgG and IgA in serum and saliva and explored associations with demographic variables. Findings The S-specific IgG prevalence was higher in serum 39% (95% CI 32 – 45%) than in saliva 30% (95% CI 24 – 36%) (P ≤ 0.003). Twenty-seven percent (55/205) of children were S-specific IgG positive in serum and saliva, 12% (25/205) were only positive in serum and 3% (6/205) only in saliva. Vaccinated children showed a higher concordance between serum and saliva than infected children. Odds for saliva S-specific IgG positivity were higher in girls compared to boys (aOR 2.63, P = 0.012). Moreover, immunocompromised children showed lower odds for S- and RBD-specific IgG in both serum and saliva compared to healthy children (aOR 0.23 – 0.25, P ≤ 0.050). Conclusions We showed that saliva-based antibody assays can be useful for identifying SARS-CoV-2 humoral immunity in a non-invasive manner, and that IgG prevalence may be affected by sex and immunocompromisation. Differences between infection and vaccination, between sexes and between immunocompromised and healthy children should be further investigated and considered when choosing systemic or mucosal antibody measurement.